"(x-y)y^2p + (y-x)x^2q=(x^2+y^2)z" is the equation to be solved for the curves
"xz=a^2" ---(1)
"y=0" ---(2)
Lagrange's auxillary equation is :
"dx\/((x-y)y^2) = dy\/((y-x)x^2)=dz\/((x^2+y^2)z)"
Solving the first two sides; we get;
"\\int (dx\/x^2)= -\\int (dy\/y^2)"
"\\implies x^3+y^3=c_1" ---(3)
Now using "-1\/(x-y),1\/(x-y);1\/z" as Lagrange multipliers, we get;
"-dx\/(x-y)+dy\/(x-y)+dz\/z=0"
"\\implies dz\/z=dx-dy\/(x-y)"
Let "x-y=t \\implies dx-dy=dt"
"\\therefore \\int dz\/z= \\int dt\/t"
On solving we get;
"t\/z=c_2 \\implies (x-y)\/z=c_2" ---(4)
Using (2) in (3) and (4) we get;
"x_3=c_1" ---(5)
"x=c_2z"
Now using (1) to substitute for z in the above equation, we get;
"x=ac^{1\/2}" ---(6)
Using (6) in (5), we get;
"c_1^2=c_2^3a^6" ---(7)
Now substituting "c_1, c_2" in (7) from (3) and (4), we get;
"(x^3+y^3)^2=(x-y)^3a^6\/z^3" ----(Answer)
Comments
Leave a comment